Development of Test Learning Resources and Physical Fitness Measurement Based on Mobile Learning - Wiwik Yunitaningrum; Mohammad Fathur Rohman (STKIP Muhammadiyah Kuningan, 2022)
The development of gadgets, especially smartphones, is rapid, and most young people are very interested in them. Young people at this time are very familiar with smartphones. An educator sees the potential in smartphones to be used as an effective, efficient and attractive medium for the transfer of knowledge if adequately developed. This research and development aim to develop learning resources for test subjects and sports measurement, test materials and physical fitness measurements. This research begins with a needs analysis with a survey method and then develops learning resources with the characteristics according to the needs analysis results. The development of this learning resource produces a product in the form of a test application and measurement of physical fitness, which is packaged in * apk, which can be installed on an Android-based mobile phone. The research method used is a research and development method with development steps designed by Borg and Gall. The researcher modified the process according to the research needs. The subjects of this study were 35 students of sports coaching education who were taking tests and physical fitness measurements. A needs analysis was carried out using a survey method using a questionnaire. Product feasibility testing was carried out using content validation by experts by providing an assessment through a questionnaire, while product testing to see the product's effectiveness used a simple experimental method in the two groups and compared the acquisition of the final test results in the two groups. The data analysis used is descriptive quantitative analysis. Based on the needs analysis data, it was found that 100% of students needed the development of this learning resource. Meanwhile, according to the results of the evaluation of the test and sports measurement, experts obtained an average score of 3.58 which means very good with a percentage of 89.44%; according to the learning technology, experts got an average score of 3.56 which means very good with a rate of 89.34%, learning experts obtained an average score of 3.67 which means very good with a percentage of 91.67%. The results of the small group trial got an average score of 3.26 which means good with a rate of 80.09%, while the results of the large group trial obtained an average score of 3.57 which means very good with a percentage of 87.96%. Thus, physical fitness mobile learning products are appropriate for use as learning resources and have proven effective in increasing students' understanding of concepts. This research and development product can still be better developed mainly in the quality of the test results analysis work system, navigation of each layer, animation, and the engraving design.